Healing from the Heart: A Burnout Prevention and Resilience Curriculum Innovation for Health Professionals in Underserved Areas - Catherine Justice; Jordan McWilliams; Roger Brown; Virginia Fowkes; Joshua D. Kamimoto; Iris Price; Ivan Gomez; Sara Poplau; Mark Linzer (Healthcare, 2026)
Background/Objectives: Healthcare burnout is a pervasive problem affecting both professionals and patients. Resilience training may be especially important for healthcare teams practicing in underserved areas. This article describes the development and pilot testing of a curriculum innovation developed as part of California Area Health Education Centers’ (CA AHEC) resilience training program. Methods: A team of experts from CA AHEC and Hennepin Healthcare Systems led the development of a whole-person approach to resilience for health professionals, trainees, and other healthcare workers in medically underserved areas. A curriculum was piloted with 7 two-hour Train-the-Trainer video conferences and 1 six-hour in-person workshop. Participants (n = 44) included representatives from 12 CA AHEC centers. Attendance was tracked, and pre/post Knowledge, Skills, and Attitudes (KSA) and Mini Z Burnout Reduction surveys were administered. An engagement survey was fielded after training. Results: Attendance averaged 26 participants per session. Engagement surveys reflected high engagement, utility, and program appreciation, with KSA surveys reflecting large gains in understanding burnout mechanisms/prevention strategies (13.5% high pre- vs. 94.7% post-, p < 0.001; Absolute difference of 81.22, 95% CI 66.87–95.58), large Cohen’s h Effect Size (ES) of 1.9) and the perceived ability to use the training to cope with stress (8.11% high pre- vs. 94.7% post, p < 0.001; Absolute Difference of 86.63%, 95% CI 73.55–99.71, large Cohen’s h ES of 2.1). Mini-Z burnout scores remained relatively unchanged. Mindfulness, mind/body approaches to resilience, community support, and system change were rated as the most impactful curricular aspects. Conclusions: This whole-person resilience curriculum represents an emerging approach to healthcare burnout. While the curriculum was greatly appreciated by attendees, working conditions and burnout remained unchanged, suggesting a need for programs that address underlying systemic stressors.